Optimum Location of Biomass Waste Residue Power Plant in Northern Region: Economic and Environmental Assessment - Shafie, S. M.; Othman, Z.; Hami, N. (International Journal of Energy Economics and Policy, 2019)
Biomass waste create huge potential in power generation. However, the critical parameter that needs to be considered in the first place is the optimum location of the plant. Hence, the aim of this study is to establish a spatial biomass resource optimisation framework so as to create a guideline for Malaysia's sustainable energy and environmental management. The most potential biomass resources that are available in the northern region of Malaysia are chosen, namely rice straw, rice husk, garden waste, corn residue, sugarcane bagasse, and coconut residue. The life cycle GHG emissions are varied from 0.02 kg/kWh to 6400 kg/kWh and life cycle cost varied from RM 0.09/ kWh up to RM 25.37/ kWh. The optimised electricity generation obtained 1.61 MW for the total power generation. The optimum design of power plant used garden waste as fuel, followed by rice straw. . Baling has the potential to generate the optimum capacity with 0.6 MW of electricity output by using garden waste as the main fuel. It means that the maximum power of electricity could be generated at each zone from 0.05 MW up to 0.6 MW. Hopefully, this result provide the guideline for decision maker to implement the renewable energy in the future. Keywords: Optimum location, biomass waste, power plant, Malaysia JEL Classifications: Q40; R11 DOI: https://doi.org/10.32479/ijeep.8338